1997
DOI: 10.1099/0022-1317-78-8-2067
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome structure and phylogenetic analysis of little cherry virus, a mealybug-transmissible closterovirus.

Abstract: The 5h-terminal genomic region (8597 nt) of little cherry virus (LChV), a mealybug-borne closterovirus, was cloned from double-stranded RNA, and its sequence determined to complete the 16 934 nt sequence of the monopartite LChV RNA genome. In the 5h to 3h direction, the sequence encompasses ORF 1a, encoding the conserved replicative domains of methyltransferase and helicase, and ORF 1b, encoding RNA polymerase. ORFs 1a and 1b partially overlap (in 0/M 1 configuration), and the LChV replicase is probably expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 20 publications
(34 reference statements)
3
59
0
8
Order By: Relevance
“…2 a). However, GLRaV-3 was not placed on the same branch as LChV, the other mealybugtransmissible closterovirus (Jelkmann et al, 1997). Rather, LChV was consistently shown to have a closer relationship with the whitefly-transmissible LIYV, using either of the phylogenetic analysis programs (MegAlign and PHYLIP).…”
Section: Helmentioning
confidence: 99%
See 4 more Smart Citations
“…2 a). However, GLRaV-3 was not placed on the same branch as LChV, the other mealybugtransmissible closterovirus (Jelkmann et al, 1997). Rather, LChV was consistently shown to have a closer relationship with the whitefly-transmissible LIYV, using either of the phylogenetic analysis programs (MegAlign and PHYLIP).…”
Section: Helmentioning
confidence: 99%
“…As first suggested for the expression of ORF1b in BYV (Agranovsky et al, 1994) and later observed in CTV , LIYV (Klaassen et al, 1995), BYSV (Karasev et al, 1996) and LChV (Jelkmann et al, 1997), a j1 ribosomal frameshift mechanism may also be used for the expression of an ORF1a\1b fusion protein in GLRaV-3. However, the socalled ' slippery ' GGGUUU sequence and the stem-loop structure that were proposed to be involved in the BYV frameshift were absent from the GLRaV-3 ORF1a\1b overlap.…”
Section: Helmentioning
confidence: 99%
See 3 more Smart Citations